The role of the language of interaction and translanguaging on attention to interactional feedback in virtual exchanges. (April 2022) - Canals, Laia
Abstract: This study sets out to examine learner-learner oral interaction during a task-based virtual exchange carried out online using video-based SCMC among 32 English and Spanish foreign language learners from two different universities. The video-recordings of three oral tasks in which learners took part in pairs were analyzed to identify, transcribe, and code language related episodes. These were divided into episodes carried out entirely in Spanish, entirely in English or by combining the use of the two languages resulting in episodes which originally started in English or Spanish but exhibited translanguaging. The aim of the study was to identify the language or language-combination mode that was more effective in eliciting interactional feedback and modified output and thus aiding in L2 development. The results indicated that English episodes exhibited slightly more explicit corrective feedback but Spanish episodes contained significantly more modified output. The presence of translanguaging had a statistically significant effect on the amount of interactional feedback and modified output in the episodes which started in Spanish. These findings suggest that English may act as the default language when the focus of attention in an oral task switches to examine a language point in virtual exchanges which has implications for L2 development.